2013
DOI: 10.5414/cn107639
|View full text |Cite
|
Sign up to set email alerts
|

Study of oxidative stress in patients with advanced renal disease and undergoing either hemodialysis or peritoneal dialysis

Abstract: Oxidative stress (OS) is directly involved in the formation of atheroma plaque and has been shown to be present since the early stages of Chronic Kidney Disease (CKD); however, the net role that dialytica techniques may play in OS process is yet to be determined. We studied three groups: hemodialysis (HD, n = 30), peritoneal dialysis (PD, n = 31), predialysis (pre-D, n = 32), and one control group (C, n = 67). Using highresolution liquid chromatography columns (HPLC), the superoxide dismutase (SOD), glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 0 publications
2
23
0
1
Order By: Relevance
“…In addition, it has also been reported that uremic toxins can reduce the activity of some repair enzymes [Lesgards et al, 2011]. Our results suggest that the HD procedure reduce some of these genotoxic sources [Puchades et al, 2013], diminishing the oxidative stress level and allowing the DNA repair enzymes to better cope with the induced DNA damage.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, it has also been reported that uremic toxins can reduce the activity of some repair enzymes [Lesgards et al, 2011]. Our results suggest that the HD procedure reduce some of these genotoxic sources [Puchades et al, 2013], diminishing the oxidative stress level and allowing the DNA repair enzymes to better cope with the induced DNA damage.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, the atheroprotective protein Apo A1 is significantly reduced in patients compared to healthy individuals. Disturbed lipoprotein profile has also been reported in several reports 14,19,20 and was ascribed to enhanced oxidative stress, malnutrition and inflammatory disorders, especially in patients subjected to maintenance HD. These lipid alterations are accompanied in our study by a significant decrease of PON1 concentration in HD patients compared to RF and controls, a fact that probably reflects the higher degree of lipid peroxidation in HD group.…”
Section: Discussionmentioning
confidence: 95%
“…Our findings also could reflect differences in response to oxidative stress in cats as a species compared to humans. For example, humans with advanced CKD show lower plasma activities of glutathione peroxidase (GPx), lower concentrations of its cofactor selenium, and lower reduced‐to‐oxidized glutathione (GSH:GSSG) ratios 6, 8, 35, 36. In contrast, cats with stage 4 CKD show a modest but significant increase in plasma GPx activities, with no decreases in serum selenium concentrations, and higher GSH:GSSG ratios 26, 37.…”
Section: Discussionmentioning
confidence: 99%